An Evaluation of the Concept of Food Chemistry, Nutrition and Health: Life Sciences-Health - S. Belyaeva, Galina; B. Bidova, Bela; Yu. Rudenko, Evgeniya; V. Fedorov, Maxim (International Journal of Life Science and Pharma Research, 2022)
It's evident that diet affects our health. Sugar, Protein, fat, and nutrients in food supply components for biochemical cycles vital to cellular function. Food chemistry refers to studying the chemical processes and interactions of all biological and nonbiological ingredients of food. Hence, this current study mainly aims to investigate the issues regarding the formation of the concept of food chemistry, nutrition, and health through the prism of the international legal aspect. To meet that aim, many general scientific approaches and methods and scientific knowledge methods, including synthesis, formal-logical approaches, induction, deduction, analysis, and system-structural, and also private scientific measures – comparative legal, historical-legal, formal-legal, and interpretative are used. Based on the results, it is established that the conceptual foundations of national security (a variety of which includes food chemistry) need constant and close scientific understanding since it is impossible to create an effective state program to guarantee the security of individuals, society and the state in various spheres of their life without a solid doctrinal basis. The points of view of the scientists on the research issue presented in the paper allow identifying the main stages of the evolution of the concept of food chemistry and security at the international level in order to determine and characterize the initial stage of the evolution of this phenomenon – the formation stage of the corresponding concept. The periodization of the development of the notion of food chemistry and security offered in the article is on the basis of such measures as legal documents of a strategic and declarative nature that demonstrate the foundations of state policy in the field of ensuring food security and some generalized doctrinal ideas on the analyzed issues adopted in the scientific community in the relevant period.